Dental Caries and Anthropometric Measurements in Children Aged between 5-14 Years - Poudyel, Pragati; Sundas, Sunanda; Dhakal, Neha; Bhusal, Pujan; Hari Subedi, Krishna (Annapurna Journal of Health Sciences, 2023)
Introduction: Dental caries is common health condition affecting billions of people in the world. Dental caries may be linked to obesity, while on the other hand, it may be linked to underweight/stunting; both are kinds of malnutrition. This study aims to find dental caries in primary and permanent dentition and nutritional status of children aged between 5-14 years.Methods: A descriptive cross-sectional study was conducted among children aged between 5-14 years who attended the Department of Pedodontic from January to April 2022.Dental caries was observed and dmft /DMFT index was calculated. Anthropometric measurements were done following WHO criteria.Body Mass Index (BMI) was calculated using age percentiles charts for boys and girls developed by Center for Chronic Disease Prevention.Results: The total participants were 200 among which 88 (44%) were female and 112 (56%) were males. The dental caries status of all BMI categories were observed, caries status was found to be more in deciduous teeth (mean dmft) than in permanent teeth (mean DMFT).BMI categories showed 39(19.5%) underweight, 122 (61%) healthy weight, 25 (12.5%) at risk of overweight and 14 (7%) were overweight.Conclusion: Dental caries status was higher in primary dentition compared to permanent dentition. Correlation between BMI and dental caries status was not significant.